Autism-linked dopamine transporter mutation alters striatal dopamine neurotransmission and dopamine-dependent behaviors - DiCarlo, Gabriella E. (J Clin Invest, 2019)
The precise regulation of synaptic dopamine (DA) content by the DA transporter (DAT) ensures the phasic nature of the DA signal, which underlies the ability of DA to encode reward prediction error, thereby driving motivation, attention, and behavioral learning. Disruptions to the DA system are implicated in a number of neuropsychiatric disorders, including attention deficit hyperactivity disorder (ADHD) and, more recently, autism spectrum disorder (ASD). An ASD-associated de novo mutation in the SLC6A3 gene resulting in a threonine-to-methionine substitution at site 356 (DAT T356M) was recently identified and has been shown to drive persistent reverse transport of DA (i.e., anomalous DA efflux) in transfected cells and to drive hyperlocomotion in Drosophila melanogaster. A corresponding mutation in the leucine transporter, a DAT-homologous transporter, promotes an outward-facing transporter conformation upon substrate binding, a conformation possibly underlying anomalous DA efflux. Here, we investigated in vivo the impact of this ASD-associated mutation on DA signaling and ASD-associated behaviors. We found that mice homozygous for this mutation displayed impaired striatal DA neurotransmission and altered DA-dependent behaviors that correspond with some of the behavioral phenotypes observed in ASD.